Corporate Governance Reforms in Nigeria: Challenges and Suggested Solutions - Adekoya , Ayodele Adelaja (Journal of Law and Governance, 2011)
This paper examines the challenges to corporate governance reforms in Nigeria from the promulgation of the Corporate and Allied Matters Act of 1990, the introduction of the 2003 Security and Exchange Commission (SEC) code of best practices in corporate governance to the 2006 Central Bank of Nigeria(CBN) code of corporate governance for banks in Nigeria. It uses related literature to review and discuss the identified challenges. It discovers that some of the challenges to corporate governance reforms in Nigeria stem from the country’s culture of institutionalized corruption and political patronage which is characterized by weak regulatory frameworks and refusal of government agencies to enforce and monitor compliance. The complexity of these challenges are compounded by the wide spread poverty and high unemployment which discourages a culture of whistle blowing. A set of suggested solutions were made including the separation of business from politics, the establishment of a special corporate affairs tribunals within the judiciary to try violators, promoting the culture of whistle blowing, enhancing business through moral education and promoting resource based development through fiscal federalism.